Comparative study of regularized and tension spline interpolation method to map surface-water salinity of Pulau Tuba, Langkawi, Kedah / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Zainolabdin, Shaidatul Najwa; Abdul Aziz, Khairul Naim; Roslani, Muhammad Akmal (Universiti Teknologi MARA, Perak, 2019)
Spatial models developed using deterministic interpolation techniques have been popularly used to predict the distribution of water quality parameters. A study was carried out to compare the performance of regularized spline and tension spline methods to estimate the surface-water salinity of Pulau Tuba, Kedah. 20 sampling points have been randomly set up to measure the level of surface-water salinity using YSI 650 Multiparameter Display System (MDS) during the period of September to November 2016. The data from half of randomly selected sampling points have been used to calibrate the model while the remaining was used to validate the model. Regularized and tension spline methods were used in this research. Based on the correlation and error analysis, the research found that the tension spline method performed better than the regularized spline method. The spatial models were then transformed into map. Based on the map accuracy assessment, the developed map of salinity produced an accuracy of 90%. The developed map using tension spline method can be used by government and private sector for future and sustainable development of Pulau Tuba, Langkawi.